The Use of Puzzle Media in BIPA Learning to Improve the Language Ability of Foreign Learners at Sangprathif Wittaya School - Aulia, Natasya Putri; Febriyana, Mutia (Journal of English Language and Education, 2025)
This study aims to improve the language ability of foreign learners through the use of puzzle media in BIPA learning in Matthayom 2 class at Sangprathif Wittaya School, Thailand. In this study, the language ability referred to in the title refer to the reading skill component. The research method used is Classroom Action Research (CAR) which was implemented in two cycles through the stages of planning, action, observation, and reflection. The research subjects consisted of 15 BIPA learners, with data collected through tests, observation, and documentation. The results of the study showed a significant increase in reading skills, especially in the aspects of word recognition accuracy, understanding of meaning, and spelling and sound relationships. The average score increased from 60 (pre-action) to 74 (cycle I) and 87 (cycle II). The percentage of learners with the very good category increased from 0% in the pre-action to 20% in cycle I and 33% in cycle II. Thus, the use of puzzle media has proven effective in improving the language ability of foreign learners in BIPA learning, especially in the aspect of reading skills.